Cavernous Sinus capillary hemangioma: Case report and literature review - Mustafa Caglar Sahin; Omer Faruk Bozkurt; Muammer Melih Sahin; Emrah Celtikci (Brain and Spine, 2023)
Introduction: Capillary hemangioma of the cavernous sinus is considered a benign vascular skull base tumor. In this case report, a patient with capillary hemangioma located in the cavernous sinus who was operated on with endoscopic endonasal approach is presented. Research question: What should be considered when planning the treatment for capillary hemangiomas located in the cavernous sinus? Material and methods: The treatment approaches applied in 12 patients with a diagnosis of capillary hemangioma located in the cavernous sinus, reported in the English literature, are reviewed in this article. We presented the clinical and radiological results of the treatments. Results: Cavernous sinus capillary hemangiomas are considered benign tumors. However, surgical treatment is preferred in the foreground because of the neurological deficits due to the compression effect caused by the mass. In the case reported by Masman et al. for the first time in the literature in 2021, they provided total excision with the endoscopic endonasal approach in the patient they first diagnosed by taking a biopsy with the endoscopic endonasal approach. In our case report, we provided total excision with endoscopic endonasal transsphenoidal approach. Discussion and conclusion: Many factors should be considered when deciding on the treatment method in these patients. Although radiotherapy is quite effective in the treatment of capillary hemangioma, surgery should be preferred, especially in symptomatic patients. In patients who cannot undergo surgery, radiotherapy is very valuable, although the long-term results are not yet known.